2017
DOI: 10.1002/asi.23981
|View full text |Cite
|
Sign up to set email alerts
|

The Closer the Better: Similarity of Publication Pairs at Different Cocitation Levels

Abstract: We investigate the similarities of pairs of articles which are co-cited at the different cocitation levels of the journal, article, section, paragraph, sentence and bracket. Our results indicate that textual similarity, intellectual overlap (shared references), author overlap (shared authors), proximity in publication time all rise monotonically as the co-citation level gets lower (from journal to bracket). While the main gain in similarity happens when moving from journal to article co-citation, all level cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…In order to create the network of documents, links between documents were weighted using the intellectual overlap equation (Colavizza, Boyack, Eck, & Waltman, 2017), and selecting the Top-15 similarities with procedures proposed by Boyack and Klavans (2010).…”
Section: Identifying Rf's and Tp'smentioning
confidence: 99%
“…In order to create the network of documents, links between documents were weighted using the intellectual overlap equation (Colavizza, Boyack, Eck, & Waltman, 2017), and selecting the Top-15 similarities with procedures proposed by Boyack and Klavans (2010).…”
Section: Identifying Rf's and Tp'smentioning
confidence: 99%
“…Co-citation has been widely used since its introduction (Boyack & Klavans, 2010) which indicates its importance in the bibliometric community. For example, Colavizza, Boyack, van Eck, and Waltman (2017) investigated the similarity of publication pairs at different co-citation levels: journal, article, section, paragraph, sentence, and bracket (including the citations). They found that the similarity of publication pairs increases monotonically as the co-citation level gets lower (from journal to bracket).…”
Section: Explanation Of the Conceptmentioning
confidence: 99%
“…Among bibliographic-based approaches, co-citation is the oldest and most widely used approach. State-of-the-art approaches incorporate content with co-citation and suggest that the actual similarity between co-cited documents is related to the proximity of citations in the text [7,8,18,19]. However, the problem with state-of-the-art approaches again arises when the content is not available as the main ingredient for these approaches is missing.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the content contains details about motivation, methods, datasets, results, sections, citation context, multiple mentions of a citation, etc. Therefore, full-text options serve as a fundamental element of these approaches and are often provided in the form of key terms [7][8][9][10]. Key terms are words or phrases that are assumed to be more meaningful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation